2011
DOI: 10.1097/ncc.0b013e3181f1ab7a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Sexual Life Reframing Program on Marital Intimacy, Body Image, and Sexual Function among Breast Cancer Survivors

Abstract: The sexual life reframing program offers an opportunity to facilitate small-group dynamics that lay the ground for further contacts leading to earlier recognition of sexual problems and active involvement for sexual health improvement for breast cancer survivors and nurses. It could be utilized for survivor education or support groups to increase sexual satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 26 publications
1
79
0
5
Order By: Relevance
“…On the basis of expert opinion, the Working Group also recommended regular stimulation (for example, masturbation) to improve sexual response. The evidence base for this recommendation consists of six publications of low-to-moderate quality [29][30][31][32][33][34] .…”
Section: Sexual Responsementioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of expert opinion, the Working Group also recommended regular stimulation (for example, masturbation) to improve sexual response. The evidence base for this recommendation consists of six publications of low-to-moderate quality [29][30][31][32][33][34] .…”
Section: Sexual Responsementioning
confidence: 99%
“…If a woman is partnered, evidence indicates that, compared with usual care, couples-based interventions are effective. The evidence base for this recommendation consists of eight publications of low-to-moderate quality [30][31][32][33]35,37,40,41 . The studies demonstrated considerable heterogeneity with respect to target (individual, couple, group), type of counselling, number of sessions, follow-up, and outcomes measurement.…”
Section: Intimacy and Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] "Sexual life is affected by psychological and physical relationships, intimacy, body image, and sexual function." [23] It is an important factor in determining the satisfaction and stability of families. [24] In this research, sexual life is defined as encompassing sex, gender identity, gender roles, eroticism, pleasure, intimacy, and reproduction, and is a part of the daily life of humans.…”
Section: Introductionmentioning
confidence: 99%